2006
DOI: 10.1007/s00422-005-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Perceptually Salient Contours using a Parallel Artificial Cortical Network

Abstract: In this paper we present a parallel artificial cortical network inspired by the Human visual system, which enhances the salient contours of an image. The network consists of independent processing elements, which are organized into hypercolumns. They process concurrently the distinct orientations of all the edges of the image. These processing elements are a new set of orientation kernels appropriate for the discrete lattice of the hypercolumns. The Gestalt laws of proximity and continuity that describe the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Both these types of connections are seen in cortex (Hunt et al, 2011). The pattern of lateral connectivity between boundary-edge detecting prediction neurons is similar to that used in many previous models of contour detection (e.g., Ben-Shahar and Zucker, 2004;Hansen and Neumann, 2008;Huang et al, 2009;Li, 1998;Mundhenk and Itti, 2005;Parent and Zucker, 1989;Ursino and La Cara, 2004;Vonikakis et al, 2006;Yen and Finkel, 1998).…”
Section: Pc/bc With Lateral Connectionssupporting
confidence: 52%
“…Both these types of connections are seen in cortex (Hunt et al, 2011). The pattern of lateral connectivity between boundary-edge detecting prediction neurons is similar to that used in many previous models of contour detection (e.g., Ben-Shahar and Zucker, 2004;Hansen and Neumann, 2008;Huang et al, 2009;Li, 1998;Mundhenk and Itti, 2005;Parent and Zucker, 1989;Ursino and La Cara, 2004;Vonikakis et al, 2006;Yen and Finkel, 1998).…”
Section: Pc/bc With Lateral Connectionssupporting
confidence: 52%
“…From a physiological point of view, the goal of this study is not to develop a contour detection model incorporated with the full V1 mechanisms including surround inhibition, spatial facilitation, feedback modulation from higher levels, temporal dynamics, etc. (Field et al, 1993; Fitzpatrick, 2000; Seriès et al, 2003; Ursino and La Cara, 2004; Vonikakis et al, 2006; Dakin and Baruch, 2009; Huang et al, 2009; Chen et al, 2014), but to clarify the different roles of orientation-selective and non-selective surround inhibition of V1 neurons in the specific task of extracting salient contours of objects from cluttered background. As the basis of this study, we demonstrated in the very beginning of this paper that, in general, V1 neurons with non-selective surround inhibition exhibit better overall performance measure due to its markedly superior ability in suppressing noised background.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, numerous neural network approaches have been proposed that are inspired by the physiology of the primary visual cortex (Ben-Shahar and Zucker, 2004;Grigorescu et al, 2003Grigorescu et al, , 2004Hansen and Neumann, 2008;Huang et al, 2009;Li, 1998;Mundhenk and Itti, 2005;Papari et al, 2007;Papari and Petkov, 2011;Petkov and Westenberg, 2003;Tang et al, 2007a,b;Ursino and La Cara, 2004;Vonikakis et al, 2006;Zeng et al, 2011a,b). A neuron in such a model has a classical receptive field (cRF), often defined using a Gabor function, that receives input from the image.…”
Section: Introductionmentioning
confidence: 99%